The Effectiveness of Socio-Affective Strategies in Students’ Speaking Proficiency - Fachri, Fachri (English Education Department, 2025)
This research had the purpose to measure the effectiveness of Socio-affective strategies to enhance students’ speaking proficiency. The method of quantitative was employed with pre-experimental approach. The experiment itself was held in the even semester of 2023/2024 academic year by involving 16 students of grade 9 of SMP Assa’adah, Radio Dalam, South Jakarta. These students were occupied in one class and selected through cluster random sampling. In collecting the data, speaking pre-test and post-test were used as the instruments. The data were analyzed statistically by using Wilcoxon test. The quantitative computation showed that the students performed better in speaking in the post-test in which they gained higher average score, that was 79.37 while in the pre-test the average score reached was only 46.87. Besides, the results of Wilcoxon test revealed that the value of Asymp. Sig. (2-tailed) of 0.001 was lower than 0.05 (0.001 < 0.05). Based on these findings, this research work concluded that Socio affective strategies were effective to enhance students’ speaking proficiency.